Pandangan Hukum Islam terhadap Upaya Penanggulangan Konflik dan Bentrok Fisik di Indonesia - Haris Haris; Abd. Rahman R.; Kurniati Kurniati (Prodi Hukum Ekonomi Syariah (Muamalah), 2022)
This paper aims to analyze the extent of the concept of overcoming conflict and physical clashes in the perspective of Islamic law. The results can be concluded that Islam as a perfect religion has a concept or guidance in tackling conflicts between fellow human beings, the concept is contained in the Qur'an and Sunnah as a guide for all Muslims. There are at least five concepts given by Islam in terms of conflict management. These concepts are tabayyun (clarifying news in order to seek clarity and clarification of information, especially information that is still unclear which can lead to slander and conflict), tahkim (mediation efforts by bringing in peacemakers to reconcile the two conflicting parties), deliberations ( conducting dialogue to make joint decisions to solve problems, namely forgiving each other to reduce conflict) and Al islah (making peace or spreading peace, for example doing good, advocating for people to make peace with one another respecting each other or Amar ma'ruf nahi mungkar)